Effect of submerged plant coverage on phytoplankton community dynamics and photosynthetic activity in situ. (1st January 2022) - Peng, Xue; Lin, Qingwei; Liu, Biyun; Huang, Suzhen; Yan, Wenhao; Zhang, Lu; Ge, Fangjie; Zhang, Yi; Wu, Zhenbin
Abstract: Restoration of submerged plants in eutrophic lakes can reduce nutrients and phytoplankton biomass in the water body. However, the effect of submerged plants on phytoplankton communities and their photosynthetic activity in situ are still poorly understood. Here, we studied the response of phytoplankton community structure and fluorescence parameters to different submerged plants coverage, the relationship of phytoplankton community and fluorescence parameters with submerged plants coverage and water physicochemical parameters were analysed in sampling area of Hangzhou West Lakes. The results showed that the coverage and biomass of submerged plants were negatively correlated with nitrogen and phosphorus contents in water body but positively correlated with total phenol content. The ratio of nitrogen to phosphorus in the study site changed greatly (32.25–124.54). In spring and summer, Oscillatoria and Leptolyngbya (Cyanophyta) were the dominant species, while in autumn and winter, the dominant species were Cyclotella (Chlorophyta), and Melosira and Cymbella (Bacillariophyta). Compared with Chlorophyta and Bacillariophyta, fluorescence parameters of Cyanophyta were more sensitive to total phosphorus, N:P ratio, total phenols, pH, and electric conductivity. Fluorescence parameters of Chlorophyta and Bacillariophyta were only affected by underwater light. Total phosphorus (TP) and N:P had a negative effect on the maximum photochemical electron yield of Cyanophyta. Furthermore, Cyanophyta was inhibited by total phenols from submerged plants. When phytoplankton were under stress, photochemical electron yield decreased significantly, whereas non-photochemical quenching increased. The structural equation model showed that the coverage of submerged plants might indirectly affect the fluorescence parameters of Cyanophyta by affecting nitrogen, phosphorus, and total phenol contents in the water body. These findings contribute to the understanding of the mechanisms underlying the impact of submerged plant restoration on phytoplankton community dynamics in subtropical eutrophic shallow lakes and provide a theoretical basis for the management of lakes. Graphical abstract: Image 1 Highlights: Total phenol content was positively correlated with submerged plants coverage. Phytoplankton biomass was negatively correlated with submerged plants coverage. 3. Submerged plants reduced Cyanophyta biomass to increase species diversity. Fv/Fm and NPQ of Cyanophyta were more affected by TN, TP, and total phenol.